Risk Factors Associated with Back Pain in School-Aged Children: A Cross Sectional Study - Dilruba Alam; Mohammed Arman; Shafiul Karim Md Elias; Md Kamrul Hasan; Palash Nag; Md Abirul Islam (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Low Back Pain (LBP) is increasingly recognized as a common health issue among children and adolescents, yet its risk factors in this age group, particularly in Bangladesh-remain poorly understood. As early-onset LBP can lead to longterm health consequences, this study aims to identify and assess potential risk factors contributing to LBP among school-aged children. Materials and methods: This is a cross sectional study done in the Department of Physical Medicine & Rehabilitation, Bangladesh Medical University, Dhaka during the period of 12 months from 3rd February 2017 to 2nd February 2018. The study population was the school children from “Willes Little Flower School” Dhaka. The sample was calculated as 96 and sampling was done by purposive sampling technique. Data cleaning validation and analysis performed using the SPSS (Version 23.0) for Windows. The result presented in tables in mean, Standard Deviation (SD) and percentages. Student’s ‘t’ tests, Chi-square test were done as required to see the level of significance. “p” value <0.05 considered as significant. Results: Among 96 school children (Mean age 11.1±2.7 years), low back pain was significantly more common in those over 10 years of age (p=0.020) with irregular physical activity (p=0.020) carrying school bags over 4 kg (p=0.029) and frequent smartphone use (p=0.042). No significant associations were found with reading habits, screen time, distance to school, mode of transport, or homework posture. Conclusion: Low back pain in school children is significantly associated with age, irregular physical activity, heavy school bags and smartphone use. Early interventions targeting these factors may help in prevention. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 79-83